Entrepreneurship Characteristics and Attitude towards Knowledge Commercialization: Evidence from Malaysia - Nawzad Sabir, Mohammed; Najm Rashid, Wirya; Al-Kake, Farhad; Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
Recently, universities have contributed to the economy of the nation through the central role of research in commercialization and economic development, as well as through traditional teaching and research roles. However, universities must provide an environment for teachers to carry out successful business activities involving technology transfer. The literature shows that there is limited attentionton exploring the business characteristics necessary to improve the commercialization of university research teachers. Therefore, to fill this gap, current research seeks to explore the relationship between the business characteristics of university research scholars and the attitude of knowledge marketing. A random sample of 94 teachers from the University of Technology Malaysia were surveyed to determine the relationship between business characteristics (i.ee,self-confidence, tolerancee ofambiguityy anduncertaintyy,creativityy,selff-reliance and the ability to adapt,opportunityyrecognitionn,innovativeness,s andmotivationn toexcel).  The research results show that leadership and self-confidence are the most important characteristics to increase commercialization. The study found that all these characteristics correlate positively with the commercial attitude of teachers. Therefore, the researcher suggests that university management should improve the business characteristics of teachers to increase the commercialization of research activities.